Comparative Study of the Physicochemical and Nutritional Parameters of Raw Milk from Three Breeds of Cows Raised in the Sub-Prefecture of Korhogo (Poro Region) - Kouamé, Maïmouna Liliane; Zoro, Armel Fabrice; Brou, Gboko Konan Gatien; Traoré, Mariam; Touré, Abdoulaye; Soro, Yadé Réné (European Journal of Applied Sciences, 2024)
Knowledge of the physicochemical and nutritional parameters of milk is essential for its use. It is in this context that the present study was conducted with a view to contributing to the food security of the people of Poro by assessing the physicochemical and nutritional quality of raw milk produced by three breeds of cattle from traditional farms in the Korhogo sub-prefecture. A survey was carried out among farmers to describe their treatment of cattle up to milking. Milk samples were taken from pasture by milking three breeds (Métis, Zébu djeli and Goudales). Physicochemical and nutrient parameters were determined using the AFNOR method. The study revealed that 56.38% of the breeders were foreigners and 52.13% had more than 10 years' experience. Traders accounted for 51.06%. Cattle were fed on pasture (100%) and milking was carried out manually (98.93%). The results of the physicochemical and nutritional parameters of the milk analysed are as follows: pH (6.70 - 6.80); acidity (16 - 18 °D); density (1.01 - 1.03); ash (6.16 - 7.90 g/L); lipids (32.20 - 45.10 g/L) and proteins (37.57 - 42.47 g/L). These results show that the milks studied comply with standards and could contribute to food security for the people of Poro.